2019
DOI: 10.1155/2019/2714286
|View full text |Cite
|
Sign up to set email alerts
|

Breakfast Intake and Factors Associated with Adherence to the Mediterranean Diet among Lebanese High School Adolescents

Abstract: The Mediterranean diet has shown to have positive health impacts on metabolic diseases and cognitive performance. However, Mediterranean countries have witnessed a decreased adherence during the past years and the adoption of a more westernized dietary pattern. The aim of this study was to evaluate the association of Mediterranean diet adherence with sociodemographic, lifestyle, and anthropometric factors among Lebanese high school adolescents. Specifically, we aimed to analyse in this group the association be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(26 citation statements)
references
References 37 publications
5
21
0
Order By: Relevance
“…In past research, favorable dietary intake characterized by consumption of fruits and vegetables, home-made meals, nuts, and adequate vitamin intake was found to predict greater academic performance [ 59 , 60 , 61 ], while a Western dietary pattern and consumption of nutrient-poor and refined food were predictive of poorer performance [ 62 , 63 , 64 , 65 ]. Our results are also in accordance with findings of previous studies that have explored adherence to the Mediterranean diet and academic achievement among Lebanese high school adolescents [ 43 , 66 ] and university students [ 67 ] showing that higher adherence was related to higher academic scores. The Mediterranean diet is considered one of the healthiest eating patterns and higher adherence has consistently been linked with better overall health and cognitive functioning [ 68 , 69 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 93%
“…In past research, favorable dietary intake characterized by consumption of fruits and vegetables, home-made meals, nuts, and adequate vitamin intake was found to predict greater academic performance [ 59 , 60 , 61 ], while a Western dietary pattern and consumption of nutrient-poor and refined food were predictive of poorer performance [ 62 , 63 , 64 , 65 ]. Our results are also in accordance with findings of previous studies that have explored adherence to the Mediterranean diet and academic achievement among Lebanese high school adolescents [ 43 , 66 ] and university students [ 67 ] showing that higher adherence was related to higher academic scores. The Mediterranean diet is considered one of the healthiest eating patterns and higher adherence has consistently been linked with better overall health and cognitive functioning [ 68 , 69 , 70 , 71 ].…”
Section: Discussionsupporting
confidence: 93%
“…When comparing the results to studies done abroad, the numbers in this study are consistent with the study done in Turkey among university students where 17.8% of students had high adherence to the MD [ 16 ], but are different than the study done among the university students in Cyprus where 26.9% had high adherence [ 17 ]. Although to our knowledge, no previous study was done in Lebanon to evaluate the level of adherence to the MD among university students, the adherence was evaluated among Lebanese high school adolescents and similar to our study, only 15.8% of the participants had high adherence [ 14 ]. Since the numbers are consistent among different age groups, this seems to be a trend of shifting dietary habits and straying away from the traditional MD in Lebanon, which raises a concern regarding future dietary habits and choices.…”
Section: Discussionsupporting
confidence: 77%
“…This study found a significant association between breakfast consumption and skipping meals with adherence to the MD. This association was established after a previous study done among Lebanese adolescents found that students who tend to skip breakfast had low adherence to the MD compared to students with regular breakfast consumption who all had high adherence [ 14 ]. Their study also concluded that not only consuming breakfast is associated with adherence to the MD, but the quality of food eaten at breakfast was also a strong predictor of the adherence to the MD.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations